Efficiency Analysis of Electric Cooperatives in the Philippines - Bautista, Carlos; Valderrama, Helena Agnes (Philippine Management Review; Vol 19 (2012), 2012)
The efficiency of electricity distribution in remote areas of the Philippines by 120 electric cooperatives (ECs) is examined using data envelopment analysis (DEA). Using data from 2001 to 2006, the study finds that most ECs can reduce all their inputs proportionately by up to 18 percent and still produce the same level of output.  Productivity in the sector has not improved significantly despite the reforms instituted in 2001 as shown by a flat trend that is discernible from the Malmquist index.  The study shows that efficiency of ECs rises with size.  This result is robust with respect to how size is defined.  The study finds that, unsurprisingly, levels of inefficiency are inversely related to system losses.  The study also shows that structural and operational characteristics significantly affect EC efficiency.  ECs are likewise found to be inefficient in the non-technical component of their distribution costs vis-à-vis their line operations and maintenance costs.
Keywords: Data envelopment analysis; Malmquist index; Electric cooperatives; Philippines